2012
DOI: 10.3389/fncir.2012.00046
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of somatostatin-immunoreactive non-pyramidal neurons in the amygdala and adjacent external capsule project to the basal forebrain: evidence for the existence of GABAergic projection neurons in the cortical nuclei and basolateral nuclear complex

Abstract: The hippocampus and amygdala are key structures of the limbic system whose connections include reciprocal interactions with the basal forebrain (BF). The hippocampus receives both cholinergic and GABAergic afferents from the medial septal area of the BF. Hippocampal projections back to the medial septal area arise from non-pyramidal GABAergic neurons that express somatostatin (SOM), calbindin (CB), and neuropeptide Y (NPY). Recent experiments in our lab have demonstrated that the basolateral amygdala, like the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 84 publications
(151 reference statements)
2
70
0
Order By: Relevance
“…However, it is worth emphasizing here that not all CBþ neurons in the amygdala have the morphology of interneurons (present results and Kemppainen and Pitkänen, 2000) and not all of them are GABAþ (Kemppainen and Pitkänen, 2000). Moreover, there is a direct evidence that some CBþ neurons are projecting neurons (Moryś et al, 1999;McDonald et al, 2012). The next important fact is that both, CBþ (present study) and GABAþ (Stefanova, 1998) neurons are in the amygdala sexually dimorphic as they are also in several other brain regions Orikasa and Sakuma, 2010;Yahr, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…However, it is worth emphasizing here that not all CBþ neurons in the amygdala have the morphology of interneurons (present results and Kemppainen and Pitkänen, 2000) and not all of them are GABAþ (Kemppainen and Pitkänen, 2000). Moreover, there is a direct evidence that some CBþ neurons are projecting neurons (Moryś et al, 1999;McDonald et al, 2012). The next important fact is that both, CBþ (present study) and GABAþ (Stefanova, 1998) neurons are in the amygdala sexually dimorphic as they are also in several other brain regions Orikasa and Sakuma, 2010;Yahr, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…Predominant SST-IR neuron decreases in the LN, known to mediate plasticity and rapid behavioral responses to fearful stimuli (86, 87) , point to abnormal processing of sensory stimuli and fear response. In addition, it is possible that small populations of LN SST-IR neurons projecting to the entorhinal cortex (88), and BN and CO SST-IR neurons to the basal forebrain (89) may be involved, potentially contributing to disrupted sensory gating in SZ (9094), and dysregulation of sleep-wake patterns in BD (9597) through the basal forebrain (98, 99), respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although the vast majority of GABAergic neurons in the BLA are local-circuit cells, a recent study reported that a small subset of SOM + neurons located in or near the external capsule projects to the basal forebrain (McDonald et al, 2012). …”
mentioning
confidence: 99%